Community-driven development of standard software modules for search and rescue robots - Kohlbrecher, S.; Petersen, K.; Steinbauer, G.; Maurer, J.; Lepej, P.; Uran, S.; Ventura, R.; Dornhege, C.; Hertle, A.; Sheh, Raymond; Pellenz, J. (2012)
The main goal of the paper is to continuously enlarge the set of software building blocks that can be reused in the search and rescue domain.